Interpretando radicalmente. Acerca de la teoría del significado de Davidson (2017)
The aim of this paper is to show the central issues of Davidson's radical interpretation theory by making use of it in a concrete example in order to see how the interpretation proposal responds to the task it was designed for. In doing this, I’ll try to show radical interpretation as an independent theory and not just as a response to other theories of meaning, as it is usually seen.